Associations Between Advanced Lung Cancer Inflammation Index and Chronic Pain: Insights From National Health and Nutrition Examination Survey (NHANES) 1999–2004 - Qiqi Huang; Liling Lin; Jingwen Li; Jianwei Lin; Zhaopei Zeng; Yuan Fu; Junxiong Qiu; Junmeng Zheng (Immunity, Inflammation and Disease)
ABSTRACT Introduction Nutrition and inflammation are known factors in chronic pain, but their combined influence is not fully understood. This study investigates the associations between advanced lung cancer inflammation index (ALI) and various types of pain, including joint pain, neck pain, low back pain, and severe headaches and migraines. Methods In this cross‐sectional study, a total of 3842 participants were recruited from the National Health and Nutrition Examination Survey (NHANES) from 1999 to 2004. Participants were categorized into three groups based on ALI tertiles: low (≤ 46.982), moderate (> 46.982 and ≤ 70.359), and high (> 70.359). Logistic regression, restricted cubic splines (RCS), and stratified analyses were employed to assess the relationship between ALI and various types of pain. Results High ALI consistently correlated with an increased risk of joint pain (fully adjusted odds ratio [OR]: 1.284; 95% confidence interval [CI]: 1.044–1.578) compared to low ALI. However, limited evidence was found in other types of pain. Stratified analyses revealed that high ALI was particularly associated with joint pain in specific demographics, including females (OR: 1.607; 95% CI: 1.205–2.144; p = 0.002), individuals aged ≥ 65 years (OR: 1.914; 95% CI: 1.254–2.923; p = 0.004), and those with a high school diploma (OR: 1.630; 95% CI: 1.171–2.268; p = 0.006). ALI also showed a positive association with multisite pain (p < 0.05), with RCS analysis revealing a linear relationship between ALI and joint pain, escalating beyond 57.85. Conclusions This study highlights the association between ALI and joint pain, particularly among females and older individuals. Furthermore, ALI may influence the presence of pain at multiple sites.